CARDIAC PATHOPHYSIOLOGY: STRUCTURE, FUNCTION, AND DISEASE MECHANISMS (Western European Journal of Medicine and Medical Science, 2024)
Cardiac pathophysiology studies the pathological processes that disrupt the normal functions of the heart and lead to various heart diseases. The heart is one of the most important organs in the body, and its primary function is to ensure blood circulation and supply oxygen and nutrients to other organs. The proper functioning of the heart is essential for the proper functioning of all systems in the body. Pathological conditions of the heart are related to various mechanisms that lead to heart failure, ischemic heart disease, arrhythmias, and other conditions. This article provides detailed information on the main mechanisms of cardiac pathophysiology, the development of heart diseases, and their therapeutic approaches.